Revitalisasi Objek Wisata Situ Gede dalam Pengembangan Wisata Alam Kota Tasikmalaya - Rakista, Putri Mutiara; Laela Susanto; Syamsu Nurkarim; Anggi Permata Karismatika; Yudi Yuslana (Program Studi Administrasi Negara Universitas Serang Raya, 2024)
Tasikmalaya City is one of the cities in West Java Province which is a development area of ​​East Priangan with the leading sectors of the craft industry, processing industry and tourism. The many tourism potentials in Tasikmalaya City have not been able to attract tourists to visit Tasikmalaya City. One of the interesting tourist attractions, which has natural beauty that is still pristine as well as historical value and many tourism potentials and is supported by a location that is easy for tourists to reach is the Situ Gede natural tourist attraction. In 2022, Situ Gede underwent revitalization carried out by the government in order to develop tourism in Tasikmalaya City. The results of the study showed that the revitalization program in the Situ Gede natural tourist area had shown progress with improvements in infrastructure such as culinary tourism spots, parking areas, and public facilities. destination promotion has also been carried out. Local communities are involved through training, and periodic socialization is carried out to ensure positive results and continuous improvement. Keywords: Nature Tourism, Revitalization, Tourism Development